Dynamic correspondence of the hang power clean to skating starts in men`s ice hockey - Laakso, L. A.; Schuster, J. G. (Strength and Conditioning Journal, 2021)
The transfer of training of the hang power clean to skating starts in men`s ice hockey was evaluated applying Verkhoshansky and Siff`s proposed criteria of dynamic correspondence to the existing research. A relatively high degree of dynamic correspondence was evidenced throughout the criteria, although with a consideration of the sagittal plane alone. Based on this evaluation, the use of the hang power clean in training increases ice hockey players` capacity to express their skill through an improvement in peak force output and an increase in rate of force development in lower limb extension and is therefore recommended to practitioners training ice hockey players.